Rapidly progressive and fatal distant spontaneous gas gangrene due to Clostridium septicum after biopsy of malignant cecal mass - Sivasubramanian, Geetha (IDCases, 2021)
Clostridium species are known to cause myonecrosis and gas gangrene which are often fatal infections in the setting of trauma but also spontaneously in certain populations such as colorectal malignancy, immunosuppression, and neutropenia. We report a case of an 83-year-old male who developed fatal and rapidly progressive gas gangrene due to Clostridium septicum within 48 h after biopsy of suspected malignant cecal mass. To our knowledge, such a drastic, rapid and fatal presentation after a diagnostic biopsy of malignant mass has not been previously reported and is something to be watchful for in suspected colon cancer cases.